Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
[tex](\frac{dy}{dx})x_{= \frac{\pi }{2} } = f^{1} (\frac{\pi }{2} ) =2[/tex]
Step-by-step explanation:
Step(i):-
Given that
[tex]f(x) = \frac{5x}{sinx} -3xsinx[/tex]
Apply (UV )¹ = UV¹+VU¹
[tex]\frac{d}{dx} (\frac{U}{V} ) = \frac{V U^{l} -VU^{l} }{V^{2} }[/tex]
Step(ii):-
[tex]f^{1} (x) = 5\frac{sin x(1)-x(cos x)}{sin^{2}x } - 3(x cos x + sin x(1))[/tex]
put [tex]x = \frac{\pi }{2}[/tex]
[tex]f^{1} (\frac{\pi }{2} ) = 5\frac{sin \frac{\pi }{2} (1)-\frac{\pi }{2} (cos \frac{\pi }{2} )}{sin^{2}(\frac{\pi }{2} ) } - 3(\frac{\pi }{2} cos \frac{\pi }{2} + sin(\frac{\pi }{2}) (1))[/tex]
we know that
[tex]cos(\frac{\pi }{2}) = 0[/tex]
[tex]sin(\frac{\pi }{2} ) = 1[/tex]
[tex]f^{l} (\frac{\pi }{2} ) = \frac{5(1-0)}{1} -3(0+1)[/tex]
[tex]f^{1} (\frac{\pi }{2} ) = 5-3 =2[/tex]
Final answer:-
[tex](\frac{dy}{dx})x_{= \frac{\pi }{2} } = f^{1} (\frac{\pi }{2} ) =2[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.